Model Technology to Performance Chain (TPC) in Implementing Accrual-Based Sistem Informasi Manajemen Daerah (SIMDA) Finance: Empirical Evidence from Local Government of Indonesia - Abdillah, Willy; Saepullah, Asep (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
This study examines TPC model in the context of utilization of accrual-based SIMDA Finance version 2.7 at Local Government of Indonesia. The success of SIMDA Finance development is not only determined by how the SIMDA Finance can process quality information, but also determined by its suitability to the work environment and its user duties. This study uses 2.056 of financial administrators of Local Government Department, consisting treasury admission, spending treasury, and operator. Online questionnaire distributed by snowball sampling with 24.5 percent of response rate and examined by Partial Least Square (PLS) technique. This study found that Job Characteristics and Techology Characteristics effect on Task-Techology Fit (TTF), Utilization, and Performance Impact. Theoretically, the study found that the TPC model was able to explain the context of public sector organizations, especially government agencies in Indonesia, outside of the organizational context when the TPC model was developed and developed earlier. Practically, the implications of research findings for stakeholders of SIMDA Keuangan are discussed further.